2007
DOI: 10.1111/j.1365-2133.2007.07919.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the nursing programme ‘Coping with itch’: a randomized controlled study in adults with chronic pruritic skin disease

Abstract: The nursing programme 'Coping with Itch' led to a reduction in the frequency of itching and scratching and to a reduction of catastrophizing and helpless coping in patients with chronic pruritic skin diseases during the period immediately following the intervention. We suggest further follow-up visits to the itch clinic to extend these results over a longer period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 28 publications
0
71
0
7
Order By: Relevance
“…While few studies have been done on psychological treatments for chronic itch, cognitive behavioural therapy and patient education may help reduce the frequency of itch [121].…”
Section: Psychological Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…While few studies have been done on psychological treatments for chronic itch, cognitive behavioural therapy and patient education may help reduce the frequency of itch [121].…”
Section: Psychological Treatmentsmentioning
confidence: 99%
“…Patient education is an important component of successful treatment of pruritus [121]. Patients should be informed that scratching creates cutaneous inflammation and should be avoided whenever possible.…”
Section: Managementmentioning
confidence: 99%
“…The programme is now widely available, reimbursed by health insurance and very popular in Germany. An educational and psychological programme, designed to reduce itch and help patients with chronic pruritic skin diseases cope with itch, and delivered by nurses, has been shown to have positive short-term effects (15)(16)(17). A recent study found long-term effects of a brief pruritus training for adult atopic dermatitis patients (18).…”
mentioning
confidence: 97%
“…Patient education plays a paramount role in the management of pruritus [62]. Patients need to be educated on how to identify and avoid exacerbating factors.…”
Section: Treatment Of Pruritus In the Elderlymentioning
confidence: 99%